2015
DOI: 10.1039/c5cp00864f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and theoretical studies of nonlinear optical crystal Sr2B5O9(OH)·H2O

Abstract: Strontium borate Sr2B5O9(OH)·H2O (space group C2, No. 5) has been synthesized in high yields using a facile hydrothermal method. The UV-Vis-NIR diffuse reflectance spectrum shows that it has a wide transparency range extending from UV to NIR with the short-wavelength cut off edge below 190 nm. Second-harmonic generation (SHG) has been measured with a 1064 nm laser using the Kurtz and Perry technique, which shows that Sr2B5O9(OH)·H2O is phase matchable and the powder SHG effect is approximately 3 times that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 62 publications
3
8
0
Order By: Relevance
“…The spectrum also shows the bending vibrations of BO 3 and BO 4 groups in the range 500–750 cm –1 . The peak assignments are in agreement with the reported borates. …”
Section: Resultssupporting
confidence: 88%
“…The spectrum also shows the bending vibrations of BO 3 and BO 4 groups in the range 500–750 cm –1 . The peak assignments are in agreement with the reported borates. …”
Section: Resultssupporting
confidence: 88%
“…The nonlinear optical crystals of strontium borate Sr 2 B 5 O 9 (OH)H 2 O have been synthesized. The DFT calculations of SHG response, nonlinear refractive index, and birefringence computed by using CASTEP package were consistent with experimentally measured values (Zhang et al, 2015). These studies show that theoretical strategies for calculating NLO response show a good agreement with the available experimental data.…”
Section: Nonlinear Optical Response: Experimental Vs Theoreticalsupporting
confidence: 79%
“…The structure of LiBa Yongjiang Wang et al [85] synthesized already reported hydrated sodium borate crystal of Na Fangyuan Zhang et. al [86] synthesized the already existing strontium borate crystal of Sr 2 B 5 O 9 (OH)H 2 O 104 and studied its characterizations by both experimental and theoretical methods. Facile hydrothermal method was used to get thigh yield Sr 2 B 5 O 9 (OH)H 2 O crystals, which belongs to C2 space group.…”
Section: Hydrated Boratesmentioning
confidence: 99%